The Exhuma: Spiritual semiosis and ritual logic in the final sequence - Pitaloka, Devanka Diaz Ayu; Setiyono, Budi; Setiawan, Aris (International Journal of Culture and Art Studies, 2026)
While film semiotics has extensively examined narrative structure, genre conventions, and audience affect, it has paid limited attention to how spiritual meaning is structurally produced within specific cinematic sequences in Asian horror cinema. This study addresses this gap by analyzing the final ritual sequence of Exhuma (2024) to examine how spiritual semiosis is constructed through the relational organization of signs rooted in East Asian cosmology. Employing a qualitative semiotic and intertextual approach, the study operationalizes Roland Barthes’ framework of denotation, connotation, and myth alongside Julia Kristeva’s concept of intertextuality to trace how ritual signs generate cosmological meaning. The final sequence is selected as a bounded unit of analysis for its narrative and spiritual culmination, which concentrates the densest configuration of elemental symbolism, bodily enactment, and verbal articulation. The findings demonstrate that the sequence is structured as a coherent ritual process consisting of cognitive recognition of elemental composition, verbal articulation of cosmological principles, and embodied enactment. At the mythic level, this configuration naturalizes a worldview in which spiritual disturbance is resolved through relational balance among elemental forces, corresponding to the operative logic of Wu Xing. Rather than making empirical claims about audience reception, this study proposes an analytical reading grounded in structural cosmological affinity, through which the film’s spiritual logic may be interpreted across cultural contexts. By integrating semiotics and intertextuality within a cosmological framework, the study contributes a model for understanding Asian horror cinema as a site of spiritual semiosis articulated through cinematic form.